Good agricultural practices (GAP) to improve rice productivity in Madagascar - CGIAR Research Program on Rice (2021)
The GAP technologies have been tested in Ambohibary and Ankazomiriotra regions of Madagascar. Yield increased from 2.2 to 4.7 t/ha in upland conditions, from 4.1 to 5.6 t/ha in lowland conditions. More than 5000 farmers trained on GAP by extension agencies.